IMPROVING SCIENCE LEARNING OUTCOMES ON THE MATERIAL OF ANIMAL CLASSIFICATION BASED ON THEIR FOOD TYPES THROUGH PICTURE MATCHING GAME MEDIA FOR GRADE IV STUDENTS OF SDN JATI GITUNG II - Reni Anggraeni Putri; Ainun Mardiah; Eltris Mistariani Gulo; Elsa Sapitri; Mawardi (STMIK Indonesia Banda Aceh, 2026)
This study aimed to improve students' learning outcomes in Natural and Social Sciences (IPAS) on the topic of animal classification based on their feeding habits through a picture-matching game for fourth-grade students at SDN Jati Gintung II. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were five fourth-grade students. Data were collected through classroom observations, learning achievement tests, and documentation. The findings revealed that the implementation of the picture-matching game significantly improved students' learning outcomes. The average score increased from 58 in the pre-cycle to 72 in Cycle I and further improved to 86 in Cycle II. Learning mastery also increased from 40% in the pre-cycle to 80% in Cycle I and reached 100% in Cycle II. In addition, the learning media enhanced students' participation, motivation, and engagement during the learning process. Therefore, the picture-matching game is an effective instructional medium for improving learning outcomes in the topic of animal classification based on feeding habits in elementary school IPAS learning.